IMPROVING WRITING SKILLS THROUGH AD TEXT THINK TALK WRITE APPROACH - Lilis Lenawati; Jesika Aprilia (IKIP Siliwangi, 2018)
Advertising loading in print or electronic media is growing rapidly nowadays. With the development of technology, advertising can be found not only in both media only. Even with the emergence of social media in Indonesia, especially today, we find a lot of ads on these social media. No less with the ads that exist on the internet has since antiquity advertising in print or electronic media were competing to market various products or services issued by various companies. Of course, in this case, they are trying to get profit from consumers who are interested in the various ads they offer. Ads generally offer products or services. Therefore it takes skill in writing ads so that the audience becomes interested and persuaded of the product or service offered. The language in the advertisement must be persuasive, easy to understand, easy to remember, and able to cause curiosity of the wider community. The Think-Talk-Write (TTW) approach provides an active learner and teacher as a motivator and facilitator so that students' communication and problem-solving skills develop. Teachers are expected to be able to choose methods, models, approaches and learning strategies that can spur the spirit of students to participate actively involved in the learning process so that later will lead to increased learning outcomes.